Fabrication of antibacterial bone scaffold based on carbonate-substituted hydroxyapatite containing magnesium from black sea urchin (Arbacia lixula) shells reinforced with polyvinyl alcohol and gelatin - Muhammad Amir Jamilludin; Juliasih Partini; Dwi Liliek Kusindarta; Yusril Yusuf (Results in Materials, 2024)
Carbonate-substituted hydroxyapatite containing magnesium (Mg–C-HAp) was introduced through dissolution-precipitation treatment of hydroxyapatite containing magnesium (Mg-HAp) based on a black sea urchin (arbacia lixula) shells as novel biogenic materials. Based on chemical composition analysis, the Mg–C-HAp formed A- and B-type CHAp, which contained high carbonate ions. The Ca/P ratio of Mg–C-HAp was 1.707, very close to the biological bone apatite of 1.71. The Mg content in Mg–C-HAp was also relatively high, with the Mg/(Ca + Mg) ratio of 0.139, which is beneficial for antibacterial agents. The morphology of Mg–C-HAp showed particles with nanosize that provide a large surface area of ion promotion. The antibacterial test revealed that the Mg–C-HAp performed high antibacterial activity against Pseudomonas aeruginosa. The Mg–C-HAp-based porous scaffolds were then fabricated using the freeze-drying method with variations of polyvinyl alcohol (PVA) and gelatin fraction. According to the physicochemical analysis, the addition of PVA and gelatin in the scaffold structure decreased the crystallinity of the Mg–C-HAp/PVA/Gel scaffold. This lower crystallinity indicates high biodegradability, which is good for new bone growth. The macropores of the Mg–C-HAp/PVA/Gel scaffold were appropriate for new bone and blood vessel formation. The micropores of the Mg–C-HAp/PVA/Gel scaffold can be a medium for cells to grow. The microporosity of the Mg–C-HAp/PVA/Gel scaffold was also suitable for cell nutrient promotion. The compressive strength of the Mg–C-HAp/PVA/Gel scaffold was sufficient for bone regeneration. The Mg–C-HAp/PVA/Gel scaffold demonstrated high antibacterial activity against P. aeruginosa, so the Mg–C-HAp/PVA/Gel scaffold can maintain the role of Mg and carbonate content for antibacterial purposes. The good physicochemical, mechanical, and antibacterial properties of the Mg–C-HAp/PVA/Gel scaffold represented its suitable characteristics for antibacterial bone scaffolds.